CELL HEALTH LEARNING BASED ON DZIKRULLOH SPIRITUAL PRACTICE œHE NING CIPTO METAPHYSICS MEDITATION, TO BUILD A STRONG BODY IMMUNITY SYSTEM - Qosyim, Ahmad; Erman, Erman; Rosdiana, Laily; Susiyawati, Enny (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
This study aimed to describe the implementation of the Spiritual Practice-Based Learning Approach to Metaphysics Meditation "He Ning Cipto" in the Cell-Level Life course to build the student’s immune system during the covid-19 pandemic. This study involved three classes of 2018 class students with a total of 90 people. This quasi-experimental research uses a "one shot case study" as a research design where there is only a treatment class without control. Data collection methods in this study include observation, tests and surveys in order to obtain data on the implementation of learning, mastery of concepts, meditation skills, and mental health. The results showed that the implementation of the learning carried out had fulfilled the syntax and obtained the dominant learning management assessment score mode of 4 from the total existing meetings. The learning outcomes test from 3 classes with 4 study topics (Cell Structure and Function, Cell Health Concepts, Body Immune System, Cipto Silent Meditation) in 7 meetings showed that students’ mastery of concepts could be achieved maximally both individually and classically with a percentage of completeness of 95, 56%. Based on rewriting data and diaries, Cipto’s Silent Meditation skills can be practiced well according to the recommended instructions and procedures. Students’ rewriting scores ranged from 78 to 100, while for student diaries they received a minimum score of 80 and a maximum of 100. The questionnaire responses given showed high Mental Attitude Health (KSM) results of 96%, High Cell/Body Health (KST) of 86% and the Happiness Scale Index is in the high category (above 34, 4) with A level between 46-50 at 29%, Level B between 40-45 at 66% and C between 34-39 at 6%. Overall, it can be concluded that this research has helped students in learning and gaining an understanding of the concept of cell health and the immune system, as well as developing silent meditation skills, to build a strong immune system for students and actors in achieving a level of mental health and mental attitude. good dohir cells/body, and pure soul happiness is born as a result of a sense of faith, and evidence of obedience and gratitude to Allah SWT for all His blessings, then the practice of meditation has an impact as a form of self-protection from various kinds of diseases including the Covid-19 virus.